(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND- When a woman's menstrual cycle comes to a stop and she is no longer able to conceive, she enters the climacteric or menopause stage. However, there are a few exceptions to this general tendency, such as women who reach menopause at an earlier age. This study conducted to check the Prevalence of frozen shoulder in post-menopausal women. METHODOLOGY- Shoulder Pain and Disability Index (SPADI), the Perceived Stress Scale, and The Epworth Sleepiness Scale were all included in the design of the form that was created. Additionally, the 36-Item Short Form Survey (SF-36), the Hamilton Anxiety Rating Scale (HAM-A), and the Menopause Rating Scale (MRS) were also incorporated into the form. Participants were given the opportunity to fill out a form, which started with a discussion of the inclusion and exclusion criteria, and continued on from there. Participants in the study were given a patient information paper after they had finished a study sample. This document included a more in-depth explanation of the research's aims, objectives, and methodology than they had previously received. Following the distribution of a patient information booklet, participants in the study provided their informed consent. The participants were requested to fill out the questionnaires, and the goniometer was used to measure the range of motion in their shoulders. After an agreed-upon amount of time had passed since all of the data had been gathered, the statistical study was carried out. RESULTS- The results of the survey indicate that the majority of women had menopause 9.89 years ago, as their average age is 55.50, their average weight is 64.71, and their average height is 5.23, with a BMI score of 11.82. The affected sides of the participants with frozen shoulder are 67 on the right, 27 on the left, and 6 on both sides. The pain ratio of the participants with frozen shoulder is 7.6 on the VAS scale. Shoulder flexion, extension, abduction, and addition on the affected side are 124.022, 2.808, 85.651, and 35.202 respectively. 81.51 is the SHOULDER PAIN AND DISABILITY INDEX score. The scores for MRS, PSS, HAMA, and EPWORTH are 12.87, 12.18, 17.26, and 10.31, respectively. There is positive correction which can be seen between the MRS scores and Duration of Menopause which mean that there is a significant effect of Menopause in frozen shoulder. CONCLUSION- The findings of the study lead the researchers to the conclusion that there is a substantial association between menopause and frozen shoulder in women. In addition, there was a reduction in stress and an improvement in quality of life as a result of menopause and frozen shoulder. Higher impacts may be shown in older participants, despite the fact that the subjects experience less stress as they become older.